ANALISIS PENERAPAN STANDAR AKUNTANSI SYARIAH PSAK NO.101 TERHADAP PENGELOLAAN TRANSAKSI KEUANGAN DI BANK SYARIAH (STUDI PADA BANK BRI SYARIAH CABANG LHOKSEUMAWE) - Nur Afni Yunita (Jurnal Akuntansi dan Keuangan, 2019)
The purpose of this study was to find out how the application of sharia accounting standards to the management of financial transactions and comparison of application of sharia accounting standards applied by PT. Bank BRI Syariah, Branch of Lhokseumawe with PSAK NO.101. The object of this research was PT. Bank BRI Syariah, Branch of Lhokseumawe. This research was conducted by using qualitative descriptive method through a case study at PT. Bank BRI Syariah, Branch of Lhokseumawe. The data used were primary data in the form of an interview. The results of this study indicated that there was no significant difference between the implementation of sharia accounting standards applied by Bank BRI Syariah, Branch of Lhokseumawe with PSAK NO.101.